2008
DOI: 10.1164/rccm.200707-1083oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of the TGF-β/Alk5 Signaling Pathway in Monocrotaline-induced Pulmonary Hypertension

Abstract: Rationale: Pulmonary arterial hypertension is a progressive disease characterized by an elevation in the mean pulmonary artery pressure leading to right heart failure and a significant risk of death. Alterations in two transforming growth factor (TGF) signaling pathways, bone morphogenetic protein receptor II and the TGF-b receptor I, Alk1, have been implicated in the pathogenesis of pulmonary hypertension (PH). However, the role of TGF-b family signaling in PH and pulmonary vascular remodeling remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
111
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 52 publications
12
111
1
Order By: Relevance
“…We have found evidence of TGF-␤ signaling up-regulation in both the mouse and human lungs, and blocking TGF-␤ is protective against experimental monocrotaline-induced PH. 6 Schistosoma-infected IL-13R␣1 Ϫ/Ϫ mice as compared with wild-type mice have an increase in CD4 ϩ T cells producing IL-4, 17 and IL-13 blockade in IL-4-deficient mice resulted in near-complete abrogation of granuloma formation. 47 Furthermore, the enhanced pulmonary vascular remodeling phenotype in S. mansoni infected IL-13R␣2 Ϫ/Ϫ mice could be due to a) increased IL-13 signaling or b) alteration of non-IL-13 cellular signaling caused by the lack of this receptor.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have found evidence of TGF-␤ signaling up-regulation in both the mouse and human lungs, and blocking TGF-␤ is protective against experimental monocrotaline-induced PH. 6 Schistosoma-infected IL-13R␣1 Ϫ/Ϫ mice as compared with wild-type mice have an increase in CD4 ϩ T cells producing IL-4, 17 and IL-13 blockade in IL-4-deficient mice resulted in near-complete abrogation of granuloma formation. 47 Furthermore, the enhanced pulmonary vascular remodeling phenotype in S. mansoni infected IL-13R␣2 Ϫ/Ϫ mice could be due to a) increased IL-13 signaling or b) alteration of non-IL-13 cellular signaling caused by the lack of this receptor.…”
Section: Discussionmentioning
confidence: 97%
“…6 Recent evidence has linked the cellular events underlying pulmonary vascular remodeling to hypoxia-like metabolic alterations, largely driven by hypoxia-inducible factor-1␣ in both experimental models 7 and in the human disease. 8 Moreover, both the human disease and experimental models have a variable contribution by inflammatory cells, whose precise pathogenetic role has not been clarified thus far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,49,50 Endothelial damage also causes a decrease in prostacyclin production, a potent vasodilator that also inhibits platelet aggregation and smooth muscle cell proliferation by increasing cAMP levels. 8,16,21,51 Recent research has revealed a genetic predisposition 52 (because not all patients with CHD develop PAH) and suggests the presence of other potential pathways involved in the pathogenesis of PAH-CHD, including downregulation of potassium channels, 53 increased matrix metalloproteinases, 54 decreased vasoactive intestinal peptide, 55 increased serotonin 56 and transforming growth factor b levels, 57 among others. 58 Potential new biomarkers and lines of therapies could result from these discoveries.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Inhibition of TGF-β signaling as a potential treatment for PAH is currently under investigation. In rats with monocrotaline-induced PAH, anti-TGF-β treatment has prevented the development of PAH, right ventricular hypertrophy, vascular remodeling and reduced the loss in exercise capacity (Long et al, 2009;Megalou et al, 2010;Zaiman et al, 2008). Specific BMP agonists or TGF-β antagonists might prove to be valuable in fighting both BMPRII mutation positive and negative PAH.…”
Section: Implications For the Treatment Of Pahmentioning
confidence: 99%